Calibration of Target-Tracking MIMO Radar Sensors by Comparison with a Narrow-Beam CW Doppler Reference - Seif Ben-Hassine; Jean-Marie Lerat; Jimmy Dubard; Pierre Betis; Dominique Renoux (Metrology)
This paper introduces a method for calibrating radar sensors in a multi-sensor cinemometer system using a reference cinemometer based on CW Doppler radar. The method involves synchronizing sensors, pairing data with reference measurements, and performing polynomial corrections. Tests conducted on various traffic sites demonstrate the accuracy and reliability of the calibration process. Results show low uncertainties compared to regulatory standards. Validation against a calibrated lidar system confirms accuracy. This method ensures precise speed measurements, surpassing regulatory requirements, and demonstrating practical applicability in real-world scenarios.